Efektivitas E-Booklet Pendidikan Kesehatan terhadap Pengetahuan Ibu Hamil Tanda Bahaya Kehamilan di Puskesmas Sonomartani Labura - Nurhabib Nurhabib; Retno Wahyuni; Rumondang Sitorus (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Early detection of high risk by health workers through quality antenatal care is one of the efforts to accelerate the reduction of MMR in Indonesia. The aim of this research was to determine "The Effectiveness of Health Education E-Booklets on Pregnant Women's Knowledge About Danger Signs of Pregnancy at the Sonomartani Labura Community Health Center in 2023. The research was conducted using a quasi-experimental research method." The design used is a one group pre test and post test design research design. The research was carried out by knowing the mother's knowledge (pretest) before being given a health education E-booklet for danger signs of pregnancy, then continuing with a final test (posttest) after being given a health education E-booklet. The research results show a P value of 0.000, meaning p 0.05, stating that the health education e-booklet is effective on pregnant women's knowledge about the danger signs of pregnancy at the Sonomartani Labura Community Health Center in 2023.